Identification of potential angiogenic biomarkers in human follicular fluid for predicting oocyte maturity - Chen, Hsuan-Ting; Wu, Wen-Bin; Lin, Jun-Jin; Lai, Tsung-Hsuan (Frontiers in Endocrinology, 2023)
Background Angiogenesis in folliculogenesis contributes to oocyte developmental competence in natural and in vitro fertilization (IVF) cycles. Therefore, the identification of key angiogenic factors in follicular fluid (FF) during folliculogenesis is clinically significant and important for in vitro fertilization. This study aims to identify the key angiogenic factors in FF for predicting oocyte maturity during in vitro fertilization. Materials and methods Forty participants who received ovarian stimulation using a GnRH antagonist protocol in their first in vitro fertilization treatment were recruited. From each patient, two follicular samples (one preovulatory follicle, > 18 mm; one mid-antral follicle, < 14 mm) were collected without flushing during oocyte retrieval. In total, 80 FF samples were collected from 40 patients. The expression profiles of angiogenesis-related proteins in FF were analyzed via Luminex high-performance assays. Recorded patient data included antral follicle count, anti-müllerian hormone, age, and BMI. Serum samples were collected on menstrual cycle day 2, the trigger day, and the day of oocyte retrieval. Hormone concentrations including day 2 FSH/LH/E2/P4, trigger day E2/LH/P4, and retrieval day E2/LH/P4 were measured by chemiluminescence assay. Results Ten angiogenic factors were highly expressed in FF: eotaxin, Gro-α, IL-8, IP-10, MCP-1, MIG, PAI-1 (Serpin), VEGF-A, CXCL-6, and HGF. The concentrations of eotaxin, IL-8, MCP1, PAI-1, and VEGF-A were significantly higher in preovulatory follicles than those in mid-antral follicles, while the Gro-α and CXCL-6 expressional levels were lower in preovulatory than in mid-antral follicles (p < 0.05). Logistic regression and receiver operating characteristic (ROC) analysis revealed that VEGF-A, eotaxin, and CXCL-6 were the three strongest predictors of oocyte maturity. The combination of VEGF-A and CXCL-6 predicted oocyte maturity with a higher sensitivity (91.7%) and specificity (72.7%) than other combinations. Conclusion Our findings suggest that VEGF-A, eotaxin, and CXCL-6 concentrations in FF strongly correlate with oocyte maturity from the mid-antral to preovulatory stage. The combination of VEGF-A and CXCL-6 exhibits a relatively good prediction rate of oocyte maturity during in vitro fertilization.